Development of wave technologies to intensify heat and mass transfer processes - Burdo, Oleg; Bandura, Valentyna; Zykov, Aleksandr; Zozulyak, Igor; Levtrinskaya, Julia; Marenchenko, Elena (Eastern-European Journal of Enterprise Technologies, 2017)
The study has proved that in order to improve the heat technologies of food production, innovative principles of energy supply are needed. The hypotheses of using wave technologies for targeted delivery of energy to elements of food raw materials are proposed. Classification of the mechanisms of heat and mass transfer intensification in food processing technologies is given. Thermophysical models of the vibrational and barodiffusion mechanisms are presented. The possibilities of a combined action of these two mechanisms are determined. It is shown that vibrational and electromagnetic fields can significantly intensify the processes of heat and mass transfer. Mechanisms, effects and mathematical models of barodiffusion and the action of vibrational fields are justified. The method of “dimensional analysis” has determined the numbers of wave similarity: modified numbers of Reynolds, Péclet, and Stanton. New numbers of similarity are proposed: the number of energy action and the dimensionless complex that takes into account the ratio of inertial forces caused by vibration and movement of the conveyor belt. On the basis of these numbers, similarities are generalized in the criterial form of a database of experimental data on extraction and drying. The methodological novelty in the processing of these experiments is the use of an effective mass transfer coefficient that takes into account the total effect of diffusion and inertial flows of liquid from the solid phase. The experiments were carried out to dry sunflower seeds in a vibration dryer. The results of drying wheat seeds and peas on the belt with electromagnetic energy sources are shown in the form of dependency graphs and mathematical models based on the database of the experimental data. The drying speed achieved was 0.4 %/min on the vibrating dryer; on the IR belt dryer, this parameter was 0.75 %/min when drying peas and 1.75 %/min when drying sludge and seeds of sunflower. The results of the complex experimental research on coffee extraction in a microwave extractor are presented in the paper. The evaluation of the completeness of extraction of extractive substances under the action of the microwave field showed the results, on average, 15 % higher than by the standard thermal method. The prospects of the combined action of the electromagnetic and vibrational fields are shown on the basis of the results for optimizing the microwave extractor.